Electrophysiology of Hypothalamic Magnocellular Neurons In vitro: A Rhythmic Drive in Organotypic Cultures and Acute Slices - Israel, Jean-Marc; Oliet, Stéphane H.; Ciofi, Philippe (Frontiers in Neuroscience, 2016)
Hypothalamic neurohormones are released in a pulsatile manner. The mechanisms of this pulsatility remain poorly understood and several hypotheses are available, depending upon the neuroendocrine system considered. Among these systems, hypothalamo-neurohypophyseal magnocellular neurons have been early-considered models, as they typically display an electrical activity consisting of bursts of action potentials that is optimal for the release of boluses of the neurohormones oxytocin and vasopressin. The cellular mechanisms underlying this bursting behavior have been studied in vitro, using either acute slices of the adult hypothalamus, or organotypic cultures of neonatal hypothalamic tissue. We have recently proposed, from experiments in organotypic cultures, that specific central pattern generator networks, upstream of magnocellular neurons, determine their bursting activity. Here, we have tested whether a similar hypothesis can be derived from in vitro experiments in acute slices of the adult hypothalamus. To this aim we have screened our electrophysiological recordings of the magnocellular neurons, previously obtained from acute slices, with an analysis of autocorrelation of action potentials to detect a rhythmic drive as we recently did for organotypic cultures. This confirmed that the bursting behavior of magnocellular neurons is governed by central pattern generator networks whose rhythmic drive, and thus probably integrity, is however less satisfactorily preserved in the acute slices from adult brains.